Comparison of Halley-Chebyshev Method with Several Nonlinear equation Solving Methods Methods - Eskandari, Hamideh (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
In this paper, we present one of the most important numerical analysis problems that we find in the roots of the nonlinear equation. In numerical analysis and numerical computing, there are many methods that we can approximate the roots of this equation. We present here several different methods, such as Halley's method, Chebyshev's method, Newton's method, and other new methods presented in papers and journals, and compare them. In the end, we get a good and attractive result.